Characterization of the general stress response in Bartonella henselae. (March 2016) - Tu, Nhan; Lima, Amorce; Bandeali, Zahra; Anderson, Burt
Abstract: Bacteria utilize a general stress response system to combat stresses from their surrounding environments. In alpha-proteobacteria, the general stress response uses an alternate sigma factor as the main regulator and incorporates it with a two-component system into a unique regulatory circuit. This system has been described in several alpha-proteobacterial species, including the pathogens Bartonella quintana and Brucella abortus . Most of the studies have focused on characterizing the PhyR anti-anti-sigma factor, the NepR anti-sigma factor, and the alternate sigma factor. However, not enough attention is directed toward studying the role of histidine kinases in the general stress response. Our study identifies the general stress response system in Bartonella henselae, where the gene synteny is conserved and both the PhyR and alternate sigma factor have similar sequence and domain structures with other alpha-proteobacteria. Our data showed that the general stress response genes are up-regulated under conditions that mimic the cat flea vector. Furthermore, we showed that both RpoE and PhyR positively regulate this system and that RpoE also affects transcription of genes encoding heme-binding proteins and the gene encoding the BadA adhesin. Finally, we identified a histidine kinase, annotated as BH13820 that can potentially phosphorylate PhyR. Highlights: The GSR was characterized in the alpha-proteobacterium Bartonella henselae . The GSR adapts gene expression patterns in conditions mimicking the flea vector. The GSR modulates expression of virulence and heme-binding genes of B. henselae . A histidine kinase (BH13820) positively regulates the GSR in B. henselae .